SYNGAP1 heterozygosity disrupts sensory processing by reducing touch-related activity within somatosensory cortex circuits. (December 2018) - Michaelson, Sheldon; Ozkan, Emin; Aceti, Massimiliano; Maity, Sabyasachi; Llamosas, Nerea; Weldon, Monica; Mizrachi, Elisa; Vaissiere, Thomas; Gaffield, Michael; Christie, Jason; Holder, J.; Miller, Courtney; et al.
Abstract In addition to cognitive impairments, neurodevelopmental disorders often result in sensory processing deficits. However, the biological mechanisms that underlie impaired sensory processing associated with neurodevelopmental disorders are generally understudied and poorly understood. We found that SYNGAP1 haploinsufficiency in humans, which causes a sporadic neurodevelopmental disorder defined by cognitive impairment, autistic features, and epilepsy, also leads to deficits in tactile-related sensory processing. In vivo neurophysiological analysis in Syngap1 mouse models revealed that upper-lamina neurons in somatosensory cortex weakly encode information related to touch. This was caused by reduced synaptic connectivity and impaired intrinsic excitability within upper-lamina somatosensory cortex neurons. These results were unexpected, given that Syngap1 heterozygosity is known to cause circuit hyperexcitability in brain areas more directly linked to cognitive functions. Thus, Syngap1 heterozygosity causes a range of circuit-specific pathologies, including reduced activity within cortical neurons required for touch processing, which may contribute to sensory phenotypes observed in patients. Michaelson et al. report that humanSYNGAP1 variation alters touch-related sensory processing. Studies inSyngap1 mice revealed circuit-specific impairments in the somatosensory cortex that underlie reduced cortical activation in response to touch.